Influence of Cervical Spine Mobility on the Focal and Postural Components of the Sit-to-Stand Task - Hamaoui, Alain; Alamini-Rodrigues, Caroline (Frontiers in Human Neuroscience, 2017)
The aim of this study was to determine the influence of cervical spine mobility on the focal and postural components of the sit-to-stand transition, which represent the preparatory and execution phases of the task, respectively. Sixteen asymptomatic female participants (22±3 years, 163±0,06 cm, 57,5±5 kg), free of any neurological or musculoskeletal disorders, performed 6 trials of the sit-to-stand task at maximum speed, in four experimental conditions varying the mobility of the cervical spine by means of three different splints. A six-channel force plate, which collected the reaction forces and moments applied at its top surface, was used to calculate the center of pressure (CP) displacements along the anterior-posterior and medial-lateral axes. The local accelerations of the head, spine and pelvis, were assessed by three pairs of accelerometers, oriented along the vertical and anterior-posterior axes. Restriction of cervical spine mobility resulted in an increased duration of the focal movement, associated with longer and larger postural adjustments. These results suggest that restricted cervical spine mobility impairs the posturo-kinetic capacity during the sit-to-stand task, leading to a lower motor performance and a reorganization of the anticipatory postural adjustments. In a clinical context, it might be assumed that preserving the articular free play of the cervical spine might be useful to favour STS performance and autonomy.